1997
DOI: 10.1111/j.1469-7793.1997.387bh.x
|View full text |Cite
|
Sign up to set email alerts
|

Emptying of Intracellular Ca2+ Stores Stimulates Ca2+ Entry in Mouse Pancreatic β‐Cells by Both Direct and Indirect Mechanisms

Abstract: Ca¥ plays a major role in stimulus-response coupling. In electrically non-excitable cells, the activation of receptors linked to phospholipid hydrolysis evokes a biphasic increase in the concentration of cytoplasmic free Ca¥ ([Ca¥]é). The first phase is due to the stimulation by inositol 1,4,5_tris-phosphate (IP3) of Ca¥ release from intracellular Ca¥ stores. The second phase results from an entry of Ca¥ across the plasma membrane (Berridge, 1993 [Ca¥]i, but had little (at 10 mÒ K¤) or no effect on the platea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
72
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 39 publications
(42 reference statements)
16
72
0
1
Order By: Relevance
“…The CPA-induced Ca 2+ influx was resistant to D600 but sensitive to extracellular Ca 2+ (Fig. 6), which is consistent with the activation of store-operated channels as described previously for wild-type beta cells [41]. We suggest that this store-operated depolarising current is sufficient to promote membrane depolarisation and thus increase the frequency of V m oscillations.…”
Section: Discussionsupporting
confidence: 70%
“…The CPA-induced Ca 2+ influx was resistant to D600 but sensitive to extracellular Ca 2+ (Fig. 6), which is consistent with the activation of store-operated channels as described previously for wild-type beta cells [41]. We suggest that this store-operated depolarising current is sufficient to promote membrane depolarisation and thus increase the frequency of V m oscillations.…”
Section: Discussionsupporting
confidence: 70%
“…The importance of PLC activity for insulin secretion is underlined by the fact that the enzyme is activated not only after exposure of islets and β-cells to various G-protein coupled receptor stimuli, such as acetylcholine/carbachol (Best and Malaisse, 1983;Hellman and Gylfe, 1986a;Best et al, 1987;Biden et al, 1987;Gilon and Henquin, 2001) and ATP (Gylfe and Hellman, 1987;Blachier and Malaisse, 1988), but also after exposure to glucose (Axen et al, 1983;Best and Malaisse, 1983;Laychock, 1983;Montague et al, 1985) and depolarizing agents (Laychock, 1983;Mathias et al, 1985;Best et al, 1987;Biden et al, 1987;Zawalich and Zawalich, 1988 (Prentki et al, 1988;Gylfe, 1991;Hellman et al, 1992;Theler et al, 1992;Miura et al, 1996) and these oscillations are characterized by a much shorter period than the glucose-induced, slow oscillations described above. Most of the [Ca 2+ ] i -elevating effect is due to IP 3 -mediated Ca 2+ mobilization from the ER, but the emptying of the stores also triggers Ca 2+ entry through store-operated channels in the plasma membrane (Liu and Gylfe, 1997;Miura et al, 1997;Dyachok and Gylfe, 2001). Although the store-operated influx of Ca 2+ only causes a small elevation of [Ca 2+ ] i , this pathway may also contribute by its depolarizing effect.…”
Section: Pip 2 and Signalling Via Phospholipase Cmentioning
confidence: 99%
“…It has recently been demonstrated that the magnitude of the current activated by intracellular pool emptying correlates with the extent of store depletion and that it can be activated even by small decreases in [Ca 2ϩ ] ER (55). In pancreatic B-cells, intracellular Ca 2ϩ pool depletion activates a small Ca 2ϩ entry and induces a depolarizing current, possibly carried by Na ϩ , that potentiates the activation of voltage-dependent Ca 2ϩ channels (17,56). This was evidenced in the present study by the observation that in the presence of 2.5 mM Ca 2ϩ in the medium, TG transformed oscillations of the membrane potential into a sustained depolarization.…”
Section: Mechanisms Of the Slow Ca 2ϩmentioning
confidence: 99%
“…Pancreatic islets were isolated aseptically after collagenase digestion of the pancreas, and when needed, they were dispersed into cells as described previously (17). Cells were allowed to attach to 22-mm circular coverslips and cultured for 2-3 days.…”
Section: Preparation Of Islets and Cellsmentioning
confidence: 99%
See 1 more Smart Citation